2004
DOI: 10.1128/mcb.24.12.5534-5547.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of mRNA Stability Using Transcription Inhibitors and Microarrays Reveals Posttranscriptional Control of Ribosome Biogenesis Factors

Abstract: Using DNA microarrays, we compared global transcript stability profiles following chemical inhibition of transcription to rpb1-1 (a temperature-sensitive allele of yeast RNA polymerase II). Among the five inhibitors tested, the effects of thiolutin and 1,10-phenanthroline were most similar to rpb1-1. A comparison to various microarray data already in the literature revealed similarity between mRNA stability profiles and the transcriptional response to stresses such as heat shock, consistent with the fact that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
377
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(403 citation statements)
references
References 65 publications
25
377
1
Order By: Relevance
“…In the model yeast Saccharomyces cerevisiae, deletion of CCR4 results in stabilization of transcripts encoding distinct functional classes (ribosome biogenesis, translation initiation, and tRNA synthesis) in response to temperature stress (13). In mammalian cells, subsets of transcripts were destabilized in response to heat shock, and induction of endoplasmic reticulum (ER) stress by treatment with tunicamycin or potentiation of ER calcium release by thapsigargin treatment triggered destabilization of a subset of mRNAs in which are included several transcripts encoding ribosomal proteins (8).…”
mentioning
confidence: 99%
“…In the model yeast Saccharomyces cerevisiae, deletion of CCR4 results in stabilization of transcripts encoding distinct functional classes (ribosome biogenesis, translation initiation, and tRNA synthesis) in response to temperature stress (13). In mammalian cells, subsets of transcripts were destabilized in response to heat shock, and induction of endoplasmic reticulum (ER) stress by treatment with tunicamycin or potentiation of ER calcium release by thapsigargin treatment triggered destabilization of a subset of mRNAs in which are included several transcripts encoding ribosomal proteins (8).…”
mentioning
confidence: 99%
“…For 3C and 4C analyses, strains were cultured to A 600 = 0.566 ± 0.07. Where required, growing S. cerevisiae 4741 cells (OD 600 = 0.6) were inhibited with phenanthroline (150 µg/ml) for 1 h. Phenanthroline causes changes to yeast transcription and mRNA stability, which mirror the rpb1-1-mediated inactivation of RNA polymerase II (POL-II) (Grigull et al, 2004).…”
Section: Growth Conditionsmentioning
confidence: 99%
“…Much less is known about the utility of such methods in S. pombe, although some studies using phenanthroline have provided evidence for inhibition of transcription (Kim et al, 2000;Kim et al, 2002). The utility of such chemical inhibitors in yeasts is somewhat limited, since a wide range of "off-target" effects may be observed that include increases in the expression of certain genes (Grigull et al, 2004) and stimulation of the stress transcriptional response (Adams and Gross, 1991). In S. pombe, temperature sensitive mutants of RNA polymerase II have been described (Mitobe et al, 2001;Mitobe et al, 1999), but studies of mRNA decay in these mutant strains have not yet been published, to our knowledge.…”
Section: Studying Mrna Decay In Yeastsmentioning
confidence: 99%
“…The mechanisms through which mRNAs are degraded in yeasts have been reviewed (Amrani et al, 2006;Coller and Parker, 2004;Garneau et al, 2007). A genome wide scan of mRNA decay that used various methods of inhibiting transcription in S. cerevisiae, including temperature-sensitive mutants of yeast RNA polymerase II and chemical inhibitors of transcription such as phenanthroline and thiolutin, has been published (Grigull et al, 2004). Much less is known about the utility of such methods in S. pombe, although some studies using phenanthroline have provided evidence for inhibition of transcription (Kim et al, 2000;Kim et al, 2002).…”
Section: Studying Mrna Decay In Yeastsmentioning
confidence: 99%
See 1 more Smart Citation